2020
DOI: 10.1016/j.chom.2019.12.007
|View full text |Cite
|
Sign up to set email alerts
|

JAK-ing into M1/M2 Polarization SteErs Salmonella-Containing Macrophages Away from Immune Attack to Promote Bacterial Persistence

Abstract: rise to autoimmunity (an immune reaction against self-epitopes). To the best of our knowledge, this study is the first to elucidate a specific mechanism linking cardiomyopathy and commensal bacteria by identifying a cross-reactive epitope between a non-pathogenic commensal bacterium and a self-epitope expressed in the heart tissue. As such, the study by Gil-Cruz et al. (2019) provides an important landmark to begin to understand etiology and mechanisms of autoimmune diseases-the implications of which are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…STAT3 phosphorylation in Y705 is required for dimerization and transcriptional activation [32]. In agreement with our data, this phosphorylation in STAT3 was shown to polarize macrophages towards an M2 phenotype in models of salmonella infection, myocardial infraction and cancer [33][34][35]. Moreover, our proteomic data indicated that LIPA was up-regulated specifically in TAMs.…”
Section: Discussionsupporting
confidence: 90%
“…STAT3 phosphorylation in Y705 is required for dimerization and transcriptional activation [32]. In agreement with our data, this phosphorylation in STAT3 was shown to polarize macrophages towards an M2 phenotype in models of salmonella infection, myocardial infraction and cancer [33][34][35]. Moreover, our proteomic data indicated that LIPA was up-regulated specifically in TAMs.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the SteE effector protein increased the polarization of M2 macrophages in granulomas ( 11 ). Recently, Brodsky et al obtained similar results that SteE protects the intracellular Salmonella from TNF-mediated granuloma clearance and hypothesized that SteE can polarize M2 macrophages ( 27 ). Furthermore, the steE -driven M2 granuloma macrophages polarization reduced iNOS mRNA expression compared to M1 granuloma macrophages, but the mRNA levels of IL-4 were significantly high ( 11 , 29 ).…”
Section: Discussionmentioning
confidence: 92%
“…Pullorum in HD-11 cells. Recent studies have evaluated the mechanisms underlying steE -mediated regulation of macrophage polarization and have provided insights into chronic infection with Salmonella ( 26 , 27 ). Furthermore, SPI-2 effector mutants ( ssaV and steE ) in S .…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines such as interferon (IFNγ) transform resting macrophages into classically activated macrophages, commonly known as the M1 phenotype. M1 macrophages amplify the cellular antigen presenting capacity, complement mediated phagocytosis, and secrete pro-inflammatory cytokines, such as tumor necrosis factor (TNF)-α, interleukin (IL-1, 6), STAT1, STAT3, IRF4, NF-κB, CIITA, CD80, CD86, and reactive nitrogen, which leads to a strong bactericidal and tumoricidal activity ( Brodsky, 2020 ; Feske et al., 2015 ; Han et al., 2017 ). Similarly, IL-4, which is mainly produced by Th2 cells, transforms naive macrophages into alternatively activated macrophages, or the M2 phenotype, which express molecules including Arginase1 (Arg1), chitinase 3, OCS1, PPARγ, STAT6, GATA3, c-MYC, HIF-1α, LXR, CD163, CD36, TGFβ, IL-10, and CD206.…”
Section: Introductionmentioning
confidence: 99%